Prenatal Versus Postnatal Tobacco Smoke Exposure and Intensive Care Use in Children Hospitalized With Bronchiolitis - Stevenson, Michelle D. (Acad Pediatr, 2016)
OBJECTIVE: Among children hospitalized with bronchiolitis, we examined the associations between in utero exposure to maternal cigarette smoking, postnatal tobacco smoke exposure, and risk of admission to the intensive care unit (ICU). METHODS: We performed a 16-center, prospective cohort study of hospitalized children aged <2 years with a physician admitting diagnosis of bronchiolitis. For 3 consecutive years, from November 1, 2007 until March 31, 2010, site teams collected data from participating families, including information about prenatal maternal smoking and postnatal tobacco exposure. Analyses used chi-square, Fisher's exact, and Kruskal-Wallis tests and multivariable logistic regression. RESULTS: Among 2207 enrolled children, 216 (10%) had isolated in utero exposure to maternal smoking, 168 (8%) had isolated postnatal tobacco exposure, and 115 (5%) experienced both. Adjusting for age, sex, race, birth weight, viral etiology, apnea, initial severity of retractions, initial oxygen saturation, oral intake, and postnatal tobacco exposure, children with in utero exposure to maternal smoking had greater odds of being admitted to the ICU (adjusted odds ratio [aOR] 1.51, 95% confidence interval [CI] 1.14–2.00). Among children with in utero exposure to maternal smoking, those with additional postnatal tobacco exposure had a greater likelihood of ICU admission (aOR 1.95, 95% CI 1.13–3.37) compared to children without postnatal tobacco smoke exposure (aOR 1.47, 95% CI 1.05–2.04). CONCLUSIONS: Maternal cigarette smoking during pregnancy puts children hospitalized with bronchiolitis at significantly higher risk of intensive care use. Postnatal tobacco smoke exposure may exacerbate this risk. Health care providers should incorporate this information into counseling messages.